A Strategic Evaluation of Clean Coal Technology as an Accelerator for Net Zero Emission Targets in the Electricity Sector - William, Milanda; Noko, Keith (Yayasan Gema Bina Nusantara, 2025)
The global urgency to mitigate climate change has pushed the power generation sector toward a rapid energy transition. This study, titled